The US Economic Statecraft Failure in the Application of the Caesar Act from 2019 to 2023 - Raden Alvy Sekar Praja (Dinasti Research, 2024)
This article aims to analyze the reasons for the failure of the United States (US) economic sanctions under the Caesar Act project, which were intended to bring about a change in the Syrian administration between 2019 and 2023. In 2019, the US implemented the Caesar Act project, which involved imposing the most comprehensive economic embargo on Syria. The Caesar Act imposed explicit restrictions on all types of foreign assistance and investment in Syria. The primary goal of the economic sanctions implemented under the Caesar Act was to exert pressure on the Syrian regime to bring about a change in government due to its severe breaches of human rights against its own citizens. Consequently, the economic sanctions had adversely affected the Syrian economy, while simultaneously exacerbating the living conditions of the people in Syria. In general, a nation's resilience weakened when it was unable to fulfil its internal stability and economic objectives. However, the Syrian government remains resolute and unwavering in its decisions. The US economic sanctions proved ineffective in addressing political transformation in Syria. This article used a qualitative methodology, utilizing triangulation techniques. This article concludes that the American economic sanctions, namely the Caesar Act, have failed due to the domestic component (stateness level) which allowed Syria to refuse or disregard the economic statecraft.